HUBUNGAN NYERI SENDI LUTUT DENGAN AKTIVITAS SEHARI-HARI DI PELAYANAN LANSIA BINJAI - Rokhima, Vitri; Purba, Dahlia (Jurnal Online Keperawatan Indonesia, 2023)
The aging process in the elderly has an impact on changes in the function of the body's organs, one of which is the function of joint movement. Decreased movement function in the elderly causes the elderly to become dependent on other people. The aim of this study was to determine the relationship between the level of knee joint pain and the daily activities of the elders. This research method is descriptive correlation of 32 respondents. Data collection was carried out using a questionnaire the Numeric Pain Rating Scale and questionnaire of independence of the elderly daily activities based on the Katz Index. The results of the study showed a relationship between the level of joint pain and daily activities in elderly people who experience knee osteoarthritis. This study found 54.5% of elderly people experienced mild pain and 35.1% of elderly people experienced mild dependence. There is a significant relationship between elderly people who experience joint pain in daily activities with p value <0.01, where the p value is smaller than 0.05 (p<0.05) and r= 0.689. The knee joint pain causes limited movement, which can cause dependency problems among the elderly and also reduce the quality of life of the elderly. ​The results of this research can be input for health care services, particularly nursing care services in the primary care unit to improve interventions with education method for the elderly about preventing osteoarthritis and knee joint pain in the elderly.